Growth and yield of castor bean fertilized with macronutrients and micronutrients - Severino, Liv Soares; Ferreira, Gilvan Barbosa; Moraes, Cássia Regina de Almeida; Gondim, Tarcísio Marcos de Souza; Freire, Whertas Saldanha de Almeida; Castro, Diego Almeida de; Cardoso, Gleibson Dionízio; Beltrão, Napoleão Esberard de Macedo (Pesquisa Agropecuaria Brasileira, 2006)
A trial was carried out at Quixeramobim, CE, with castor bean plants (Ricinus communis L.), cv. BRS Nordestina, in order to evaluate the effect of mineral fertilization with macronutrients and micronutrients on growth, sexual expression and yield. A randomized blocks design with three replications and 14 treatments originated from a baconian matrix was adopted. Reference doses were 50 kg ha-1 of N, 60 kg ha-1 of P and 40 kg ha-1 of K. Data on growth, sexual expression, yield and oil content were measured. Characteristics related to plant growth were low affected by treatments except in the absence of fertilization. Seed oil content increased in response to P doses. Higher availability of N and K promoted some alteration in the sexual expression favorable for increasing yield. Yield increased from 1,072 to 2,298 kg ha-1 due to N fertilizer.
Keywords: Ricinus communis; sexual expression; oil content